2009
DOI: 10.1371/journal.pone.0007185
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression in a Large Urban South Indian Population — The Chennai Urban Rural Epidemiology Study (Cures – 70)

Abstract: BackgroundIn India there are very few population based data on prevalence of depression. The aim of the study was to determine the prevalence of depression in an urban south Indian population.Methods and FindingsSubjects were recruited from the Chennai Urban Rural Epidemiology Study (CURES), involving 26,001 subjects randomly recruited from 46 of the 155 corporation wards of Chennai (formerly Madras) city in South India. 25,455 subjects participated in this study (response rate 97.9%). Depression was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
180
10
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(221 citation statements)
references
References 37 publications
29
180
10
2
Order By: Relevance
“…10,11,19,21,29 In our study, 70 % were females and among them, 69.9 % were widows. The probable reason for this high number of females in our study is due to enhanced longevity among females.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…10,11,19,21,29 In our study, 70 % were females and among them, 69.9 % were widows. The probable reason for this high number of females in our study is due to enhanced longevity among females.…”
Section: Discussionmentioning
confidence: 45%
“…This finding was consistent with previous studies. 13,29,31,32 Recent stressful life events should be identified and suitable support, self-help groups, and counseling need to be in place in the community.…”
Section: Discussionmentioning
confidence: 99%
“…15 A large population-based study from South India, which screened more than 24,000 subjects in Chennai using patient health questionnaire (PHQ)-12 that the overall prevalence of depression was 15.1% which was conducted in general population and the prevalence of depression in the present study will be higher as it is in medically ill subjects. 16 Bivariable analysis showed that gender, education, marital status, socio economic status, physical activity, uncontrolled Blood pressure and duration of hypertension was associated with depression among hypertensives. Female gender was found to be a risk factor for the development of depression with significant odds ratio of 2.33. WHO facts on gender and health also emphasis that depression is twice common in females.…”
Section: Resultsmentioning
confidence: 99%
“…Comparatively more unipolar cases were female and bipolar were male, which is in concordance with few other clinic-based studies but contradictory to many other studies which were basically population based. [18][19][20][21][22] Majority of the cases were of the productive age group, which might had led to a tremendous loss for the societal development.…”
Section: Discussionmentioning
confidence: 99%